A brief overview of China's ETS pilots : deconstruction and assessment of Guangdong's greenhouse gas emission trading mechanism /: deconstruction and assessment of Guangdong's greenhouse gas emission trading mechanism. ([2019]) - Zhao, Daiqing; Wang, Wenjun; Luo, Zhigang
No abstract available